Role Of Prosecutor's Laws in Submission of Civil Services Against Submission of Civil Services in Completion of Stories - Dian Wahyuni; Ismansyah Ismansyah; Yussy Adelina Mannas (Universitas Slamet Riyadi, 2020)
Corruption or commonly referred to as